2023
DOI: 10.3390/foods12091925
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Optimization of Ultrasound-Assisted Extraction of Bioactive Compounds from Allium sativum Leaves Using Response Surface Methodology and Artificial Neural Network Coupled with Genetic Algorithm

Abstract: This study explains the effect of ultrasound on the extraction of the bioactive compounds from garlic (Allium sativum L.) leaf powder. The experiment was carried out by varying the ultrasound amplitude (30–60%), treatment time (5–15 min), and ethanol concentration (40–60%) required to obtain the maximum extraction yield of total phenol content (TPC), total flavonoid content (TFC), and antioxidant activity. Rotatable central composite design (RCCD) provided experimental parameter combinations in the ultrasound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…1 e-f shows that increasing the ethanol content by up to 50% increases the antioxidant activity determined by ABTS, but an additional decrease can be observed ( Fig. 1 d-f), which may be due to the negative effect of the terms ( Shekhar, Prakash, Singha, Prasad, & Singh, 2023 ). In addition, it is observed that the interaction effects do not present significant effects ( 0.05 ) on the antioxidant activity ( Table 4 ), which indicates that the antioxidant activity was individually affected by the ethanol concentration and not by their interactions for the antioxidant activity determined by ABTS of Avocado seeds ( Weremfo et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
“…1 e-f shows that increasing the ethanol content by up to 50% increases the antioxidant activity determined by ABTS, but an additional decrease can be observed ( Fig. 1 d-f), which may be due to the negative effect of the terms ( Shekhar, Prakash, Singha, Prasad, & Singh, 2023 ). In addition, it is observed that the interaction effects do not present significant effects ( 0.05 ) on the antioxidant activity ( Table 4 ), which indicates that the antioxidant activity was individually affected by the ethanol concentration and not by their interactions for the antioxidant activity determined by ABTS of Avocado seeds ( Weremfo et al, 2020 ).…”
Section: Resultsmentioning
confidence: 93%
“…This phenomenon can be attributed to the breakdown of the plant cell wall, facilitated by water's role as a swelling agent, leading to enhanced extraction of phenolic compounds. The solvent ethanol aids in dissolving the polyphenols by disrupting the solid-solvent contact area, further enhancing the extraction process [45]. Ultrasonication has shown similar results when investigated against conventional extraction methods in food processing [46].…”
Section: Impact On Total Phenolic and Flavonoid Contentmentioning
confidence: 98%
“…Although there are numerous HBA:HBD combinations that can solubilize proteins, it is currently unclear how all of those properties interact to affect protein extraction. In order to maximize the extraction of biomolecules from plant sources, new strategies incorporating computer-aided technology, such as machine learning, are very helpful when analyzing complicated data with various parameters (Ma et al, 2023;Shekhar et al, 2023). Shi et al (2022) successfully employed a machine learning algorithm to predict DES viscosity by considering the basic properties (i.e., molar mass of HBA and HBD, HBA:HBD molar ratio, and temperature), molecular fingerprint of the HBA:HBD composition, and water content as the model input.…”
Section: Factors Influencing Des-mediated Protein Extractionmentioning
confidence: 99%